PENGARUH MODEL PEMBELAJARAN KOLABORATIF NUMBERED HEADS TOGETHER BERBASIS HOT SEAT TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADIST - Siti Salamah; Fashi Hatul Lisaniyah (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
At MI Islamiyah Nguwok, traditional lecture techniques still predominate while teaching Al-Qur'an Hadith, which tends to lower students' interest in the subject. The purpose of this study is to investigate how students' motivation in learning is affected by the Numbered Heads Together’ (NHT) learning paradigm, which is based on the Hot Seat technique. A pre-experimental one-group pretest–posttest design was used in the study's quantitative methodology. There were twenty-four students involved. Questionnaires were used to gather data, and a paired sample t-test was used for analysis. Hₐ was accepted and H₀ was denied. Thus, it can be claimed that has a significant influence on students' motivation to study the Qur'an and Hadith.